Bright and Long‐Lived Emission from a Starburst‐Type Arylborane‐Appended Polypyridyl Ruthenium(II) Complex. Issue 32 (31st August 2017) - Nakagawa, Atsushi; Ito, Akitaka; Sakuda, Eri; Fujii, Sho; Kitamura, Noboru
Abstract : The starburst‐type arylborane‐appended polypyridyl Ru II complex [Ru4, 7‐bis(dimesitylboryldurylethynyl)‐1, 10‐phenanthroline3 ] 2+ (1 ) was synthesized, and its spectroscopic and photophysical properties were evaluated. In the excited state of the complex, intramolecular charge transfer (CT) between the π orbital of the aryl group and the vacant p orbital of the boron atom [π(aryl)–p(B) CT] interacts synergistically with metal‐to‐ligand charge transfer (MLCT). The synergistic CT interactions in1 are more effective than those in previously reported arylborane‐appended polypyridyl Ru II complexes and lead to bright (molar absorption coefficient of the MLCT band = 7.2 × 10 4 m –1 cm –1, emission quantum yield = 0.29) and long‐lived emission (8.7 µs) of1 in CH3 CN at 298 K. The unique emission characteristics of1 are discussed in detail together with its electrochemical properties and time‐dependent DFT (TD‐DFT) calculations. Abstract : A starburst‐type arylborane‐appended polypyridyl Ru II complex simultaneously shows a high emission quantum yield and a long emission lifetime (8.7 µs). In the excited state of the complex, intramolecular charge transfer between the π orbital of the aryl group and the vacant p orbital of the boron atom interacts synergistically with metal‐to‐ligand charge transfer.